Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1123/jpah.10.7.1016
|View full text |Cite
|
Sign up to set email alerts
|

Prescribed Exercise: A Prospective Study of Health-Related Quality of Life and Physical Fitness Among Participants in an Officially Sponsored Municipal Physical Training Program

Abstract: Participation in group-based prescribed exercise program for 3 months may improve physical fitness and HRQoL significantly in short and long terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 29 publications
2
18
2
8
Order By: Relevance
“…The HLCs are easily accessible, and people can attend the service through referral from a general practitioner (GP) or other health care providers or by self-referral (Norwegian Directorate of Health, 2016). The HLCs offers knowledge-based support for changing living habits and coping with health challenges through individual- and group-based counselling and activities, and use client-centred counselling approaches to promote the participants’ internal motivation, empowerment and coping (Abildsnes, Meland, Samdal, Stea, & Mildestvedt, 2016; Følling, Solbjør, & Helvik, 2015; Lerdal, Celius, & Pedersen, 2013; Norwegian Directorate of Health, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The HLCs are easily accessible, and people can attend the service through referral from a general practitioner (GP) or other health care providers or by self-referral (Norwegian Directorate of Health, 2016). The HLCs offers knowledge-based support for changing living habits and coping with health challenges through individual- and group-based counselling and activities, and use client-centred counselling approaches to promote the participants’ internal motivation, empowerment and coping (Abildsnes, Meland, Samdal, Stea, & Mildestvedt, 2016; Følling, Solbjør, & Helvik, 2015; Lerdal, Celius, & Pedersen, 2013; Norwegian Directorate of Health, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is a lack of studies evaluating the effect of HLC programmes. Results from a prospective intervention study with a 12-month follow-up indicated that participation in a group-based prescribed PA programme for 3 months significantly improved physical fitness and health-related quality of life (HRQoL) post intervention and at follow-up [26]. However, the generalizability of these findings is affected by high drop-out rates and should therefore be interpreted with caution.…”
Section: Introductionmentioning
confidence: 99%
“…The study of health-enhancing behavior and lifestyle in adolescents from North Indian City draws attention to the fact that some healthenhancing types of behavior (physical exercise and healthy diet), but also those health-damaging ones (smoking and use of alcohol) adopted and adapted in the period of adolescence are often preserved until late adulthood (70% of deaths has its roots in the habits related to health behavior solidified in this crucial developmental stage (Raj, Senjam, & Singh, 2013). As opposed to later life periods, this stage also involves more health-threatening behavior and risky attitudes to one´s own health (Haskell et al, 2007;Lerdal, Celius, & Pedersen, 2013). That is why the importance of influence of social support on an individual´s health raises in this stage of development, since, apart from its indirect influence, it can be also significantly demonstrated by its direct influence during adolescence − e.g.…”
Section: Introductionmentioning
confidence: 99%